Pemberdayaan Kelompok Tani Pattunggalengan di Kabupaten Takalar melalui inovasi budidaya bawang merah - Rahmawati Rahmawati; Darmawan Risal (Riau Journal of Empowerment, 2021)
Shallots are one of the horticultural crops cultivated by the Pattunggalengan Farmer Groups in Banggae Village, Takalar Regency, whose production is decreasing. The decline in production is influenced by application inorganic systems and use of seeds that are not superior because they come from multiplied tillers and cultivation systems that are semi-manual. The purpose of this activity’s to provide counseling and assistance on onion cultivation innovation in Pattunggalengan Farmer Groups, from selecting seeds, making planting demonstration plots, fertilizing, planting, watering and harvesting. The method used was discussion group forum and making of planting demonstration plot using Super Philip and drip irrigation. The soil pH condition demonstration plot location was 6.5, which classified optimal but was given organic fertilizer to provide macro nutrients, shallot seeds by giving mankozeb fungicide with drip irrigation watering system on each sample bed. The yield obtained with 100 kg and the number of seeds were 250 kg/100 m2. The counseling and mentoring that was carried out made the Pattunggalengan farmer know good soil cultivation, superior seeds and production resulting from the innovation of shallot cultivation